Promoting Innovation in the Mobile Sector : A Step-By-Step Methodology to Implement a Mobile Innovation Roadshow - World Bank (Washington, DC, 2015)
Access to mobile communications has been linked with economic growth and the industry itself boosts local economies by creating high-value direct and indirect jobs. As part of its mobile innovation program, infoDev developed the concept of the mobile innovation roadshow with the overall objective to stimulate the development of an innovation and entrepreneurship ecosystem for mobile applications enterprises by introducing business and technical concepts relevant to startups in the mobile industry via a series of short events. The roadshow was developed in partnership between the Southern Africa innovation support (SAIS) program and infoDev. The objective of this practical guide is to provide a tool for interested parties on how to plan, organize, implement, and evaluate a mobile innovation roadshow. The guide presents a generic methodology that can be used in any country context. It provides lessons and best practices based on the experiences of implementing mobile innovation roadshows in four countries in Southern Africa: Mozambique, Botswana, Namibia, and Zambia.